An appraisal of religion and psychiatry since 1954 - Hiltner, Seward (Journal of religion and health, 1965)
The conclusion needs to be a word of warning rather than of congratulation. During the entire past generation, the slow but clear progress in constructive relationship between religion and psychiatry has been mainly a matter of increased understanding, and then mutual co-operation, between cleargymen and psychiatrists. But clergymen are not all there is of religion, and psychiatrists are not all there is of psychiatry. While, in the years ahead, the mutual understanding and co-operation between psychiatrists and clergymen must be increased, much more must be done on the larger scale: mutual understanding and co-operation between the whole of the psychiatric team, and the whole of the religious "team." I believe that taking the full implications of "team" into account is the most important consideration in planning for these years ahead.